ANALISIS GAYA KEPEMIMPINAN DEMOKRATIS DAN MOTIVASI KERJA TERHADAP KINERJA PENGELOLA DESA WISATA DI KECAMATAN TURI - rachmad widaryanto (Prodi Magister Manajemen FE-UST, 2021)
This study aims to empirically examine the effect of democratic leadership style, work motivation on intervening job satisfaction performance. The sample of this study was the managers of 13 tourist villages in Turi District, Sleman Regency, Special Region of Yogyakarta. The total sample of 72 respondents was obtained using the slavin method, while the sampling technique was by using a stratified sampling method. Data collection was carried out by distributing questionnaires to all respondents. The analysis in this research uses descriptive analysis method and inferential analysis method using Partial Least Square (PLS). The results of this study indicate that the democratic leadership style, and work motivation significantly positively influence job satisfaction. Leadership style and work motivation significantly positively influence performance. While job satisfaction has a positive effect on the performance of the tourism village managers in Turi District. Keywords: democratic leadership style, work motivation, job satisfaction, performance